Pengaruh Brand Ambassador Twice Terhadap Minat Beli Dengan Brand Image Sebagai Variabel Intervening Pada Produk Kecantikan Scarlett: Studi Kasus Pada Konsumen Produk Scarlett Di Kecamatan Padang Hilir Kota Tebing Tinggi - Benhart Nainggolan; Suwadi Suwadi (Management And Business Progress, 2026)
This research aims to determine "The influence of the Twice Brand Ambassador on Purchase Interest with Brand Image as an Intervening Variable in Scarlett Beauty Products (Case Study of Scarlett Product Consumers in Padang Hilir District, Tebing Tinggi City)". The sample determination method used in this research was by using the Cochran formula of 96 samples who were consumers of Scarlett products in Padang Hilir District, Tebing Tinggi City. Based on the results of the analysis of hypothesis 1, it can be concluded that the first hypothesis is accepted, meaning that the Brand Ambassador variable influences the Brand Image variable. Based on the results of the analysis of hypothesis 2, it can be concluded that the second hypothesis is rejected, meaning that the Brand Ambassador variable has no effect on the Purchase Interest variable. Based on the results of the analysis of hypothesis 3, it can be concluded that the third hypothesis is accepted, meaning that the Brand Image variable influences the Purchase Interest variable. Based on the results of the analysis of hypothesis 4, it shows that the indirect influence between the Brand Ambassador variable on Buying Interest through Brand Image is accepted rather than the direct influence between the Brand Image variable on Buying Interest.